ANSWER:
(3, -6)
Explanation:
We have the following system of equations:
![\begin{gathered} 4x+y=6 \\ -5x-2y=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sy01l0m9l7b73p14gk24lyi88kipryhr7z.png)
We must solve by the elimination method, to do this we must multiply the first equation by 2 and then add both equations, to eliminate the variable y, just like this:
![\begin{gathered} 2\cdot(4x+y=6)\rightarrow8x+2y=12 \\ \text{ Therefore:} \\ 8x+2y-5x-2y=12-3 \\ 3x=9 \\ x=(9)/(3) \\ x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qf6fsy4abkslvphc1rzvmknbp1u9m4265r.png)
Knowing the value of x, we can calculate the value of y, substituting in the first equation:
![\begin{gathered} 4\cdot3+y=6 \\ y=6-12 \\ y=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cc3gk1ujws4ezf6ojrzd0d5lntg6c1s59a.png)
Therefore, the solution of the system is (3, -6)